QOLP-02. INSURANCE STATUS IMPACTS THE ECONOMIC BURDEN AND SURVIVAL OF GLIOBLASTOMA PATIENTS WITH HEALTH INSURANCE. (5th November 2018) - Chandra, Ankush; Young, Jacob; Dalle Ore, Cecilia; Lau, Darryl; Rick, Jonathan; Dayani, Fara; Nguyen, Alan; Garcia, Joseph; McDermott, Michael; Berger, Mitchel; Aghi, Manish
Abstract: INTRODUCTION: Glioblastoma carries a high economic burden for patients and caregivers. We investigated the hospital costs of surgery for newly-diagnosed glioblastoma patients based on insurance status. METHODS: Retrospective review of GBM patients undergoing first resection at UCSF and corresponding hospital charges from 2010–2015. RESULTS: Of 227 patients (median age= 62; females= 37.9%), 31 (13.7%) had Medicaid, 94 (41.4%) had Medicare, and 102 (44.9%) had private insurance. Medicaid patients had 30% higher mean overall hospital costs for resecting GBM compared to non-Medicaid insurance patients ($50, 285 vs $38, 800; p= 0.015). Sub-cost analysis revealed Medicaid patients had higher ICU, OR and imaging costs versus non-Medicaid insured patients ($13, 400/$16, 470/$2, 182 vs $9, 700/$14, 770/$1, 357; p= 0.01/p= 0.03/p< 0.0001). Kaplan-Meier survival analysis showed Medicaid patients had the shortest overall survival (10.7 months, Medicare = 12.8 months, Private insurance = 15.8 months; p=0.02). Tumor diameter at diagnosis was largest for Medicaid (4.7 cm) versus Medicare (4.1 cm) and privately insured patients (4.2 cm; p=0.03). Only 67.74% of Medicaid patients had PCPs versus 91.5% and 86.27% of Medicare and privately insured patients, respectively (p=0.004), at their initial visit to our institution. Medicaid patients had longer overall and ICU lengths of stay (6.9 and 2.6 days) versus Medicare (4.0 and 1.5 days) and privately insured (3.9 and 1.8 days; p < 0.01) cohorts. Moreover, Medicaid patients had similar comorbidity rates as Medicare patients (67.8% vs. 67.18%), but both groups had higher comorbidity rates than privately insured patients (40.4%; p< 0.0001). CONCLUSIONS: Despite higher surgical costs and longer lengths of stay, GBM patients with Medicaid have poorer survival. This may reflect that these patients lacking PCPs and, thus, having more comorbidities and presenting later in the disease course with larger tumors consume more hospital resources such as OR time and confer increased operative risk.